1994
DOI: 10.1007/bf01717454
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behavior of health care personnel regarding influenza vaccination

Abstract: This paper reports the results of a study conducted by the Italian Association for Immune-Prophylaxis Promotion (AIP.I) with the aim of surveying the attitudes and perceptions of Italian health care workers regarding the use and efficacy of influenza vaccine. The results clearly show that a high proportion of the questioned health care workers showed a general lack of concern about the severity of the disease. Doubts about vaccine efficacy and fear of post-vaccination side effects were also observed to have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 11 publications
2
19
0
2
Order By: Relevance
“…The feeling of being healthy and having good natural defenses towards influenza infection was expressed by 6-58% of HCW (16 studies). In Switzerland, [30] Canada, [21,25] and Italy, [29] this response was notably frequent, in physicians and nurses alike [29]. · The times/locations of vaccination were unsuitable for 6-59% of HCW.…”
Section: Discussionmentioning
confidence: 96%
“…The feeling of being healthy and having good natural defenses towards influenza infection was expressed by 6-58% of HCW (16 studies). In Switzerland, [30] Canada, [21,25] and Italy, [29] this response was notably frequent, in physicians and nurses alike [29]. · The times/locations of vaccination were unsuitable for 6-59% of HCW.…”
Section: Discussionmentioning
confidence: 96%
“…This is similar to previous findings but appears not to have been successfully tackled as yet. 17,18,30,31 Staff training may therefore have a positive impact on vaccination coverage.…”
Section: What This Study Addsmentioning
confidence: 98%
“…16 Previous research on low uptake rates has particularly focused on flu vaccination and has shown that coverage varies depending on staff group. 17 A variety of barriers have been suggested including personal influences such as doubts regarding vaccine efficacy, lack of personal knowledge and low concern about disease severity; 18,19 this is often despite regular extensive staff vaccination campaign, including messages around safety and efficacy, for influenza. Organizational influences such as inconvenient locations and times for vaccination clinics also affect uptake 19,20 and peer vaccinators have been trialled in many areas; for example in Abertawe Bro Morgannwg University Health Board, which covers the city of Swansea and the surrounding areas, their introduction contributed to increased flu vaccination coverage from 22% to 40% but were met with hostility by some staff (personal communication).…”
Section: Introductionmentioning
confidence: 98%
“…This situation is also more specific to nurses and ancillary workers. 10,14 However, this situation of weakness compared with the physicians and to other countries, should be seen as an opportunity to improve the vaccination rate for seasonal influenza significantly. This should be done by intervening on the category which Protection of other people is considered more or less like patients protection, and it is strange that HCW do not consider how fragile and sensitive patients are compared with ordinary people from an influenza.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…5 Factors enhancing vaccination are protection of patients, family, self and other people, being a healthcare worker, belonging to the elderly population or being affected by a chronic disease, and finally acknowledging the protctive effect of vaccination. 5,[9][10][11] Ideas preventing vaccination are to not caring about influenza, having doubts about vaccine efficacy, being afraid of adverse effects, being opposed to vaccination, forgetfulness, considering that vaccine do not have a protective effect and thinking of influenza as a mild disease. 5,[9][10][11] The aim of this study is to conduct a systematic review and meta-analysis in order to: (1) estimate the prevalence of influenza vaccinations among nurses and ancillary workers in Italy, by using a pooling of data coming from observational studies; (2) explore all the possible enhancing and hindering factors associated with this kind of vaccination among nurses.…”
Section: Introductionmentioning
confidence: 99%